Design of an LCL-filter for grid-connected hybrid ANPC inverters - Kim, Ye Ji; Kim, Sang Hun; Bae, Kyu Chul; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2019)
This paper proposes an LCL-filter design procedure for three-level hybrid active neutral point clamped (ANPC) inverters in grid-connected systems. Although more active switches are used, the hybrid ANPC inverter help to balance the loss distribution. The hybrid ANPC inverter consist of silicon insulated gate bipolar transistors (Si IGBTs) and silicon carbide metal-oxide-semiconductor field effect transistors (SiC MOSFETs). The hybrid ANPC inverter can be operated at high switching frequency compared to neutral-point-clamped (NPC) inverters. Therefore, the hybrid ANPC inverter has low switching losses due to the physical characteristic of the SiC MOSFETs. The inverter-side inductance is determined by the ripple factor of the hybrid ANPC inverter. To calculate the ripple factor, the output current ripple is required. In the grid-connected inverter, the output current ripple is related to the grid voltage, output phase voltage, and inductance. Thus, the inductance is calculated by using the equation of ripple factor. The filter capacitance is designed by the reactive power absorption ratio and the grid-side inductance is determined by the ripple attenuation factor. The effectiveness of the proposed LCL-filter design method for the hybrid ANPC inverters was verified by the simulation results and experimental results.
Keywords: Active neutral point clamped; Current ripples; Grid filters; Hybrid power; LCL filters; Silicon carbides (SiC); Active neutral point clamped (ANPC); Current ripple; Grid filter; Hybrid power stage; LCL-filter; Silicon Carbide(SiC)